ANALISIS RISIKO PRODUKSI PADI DALAM PENGEMBANGAN ASURANSI USAHATANI PADI (AUTP) DI DESA PANCA ARGA, KECAMATAN RAWANG PANCA ARGA, KABUPATEN ASAHAN - Saragih, Ika Rosalia; Chalil, Diana; Ayu, Sri Fajar (Jurnal AGRISEP, 2018)
Rawang Panca Arga Sub-district, Asahan Regency is recorded as the most highly participated farmers in North Sumatra paddy centers in Rice Farming Insurance (AUTP) Program. This stems from their experience in suffering from pest attack and flood. However, the participation tend to decrease as the threshold for receiving the insurance coverage is considered too high ?75%, while in fact the range of loss is around 30%-40%. To analyze such a condition, this study collected data from 50 paddy farmer samples, and analyze the risk map with production risk probability and impact, namely Z-score and Value at Risk. The results show that the risk probability due to pests and climate change are 18,41%and0.60%, respectively, while the impacts are Rp 3,764,495 and Rp 1.256.036, respectively. Only 2 out of 50 farmers experienced loss more than 75%, in which the insurance could only cover 42%-78% of the production costs.